Diastereoselective aminooxygenation and diamination of alkenes with amidines by hypervalent iodine(III) reagents - Chen, Hui (2015)
Diastereoselective anti-aminooxygenation and anti-diamination of alkenes with amidines were enabled by hypervalent iodine(III) reagents such as PhI(OCOR)2 and PhI(NMs2)2, respectively. The present transformation offers diastereochemically pure dihydroimidazoles divergently from E- and Z-alkenes.